Strategi Pembelajaran Berbasis Children's Well Being Pada Pendidikan Anak Usia Dini - Trya Ardiani; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Learning strategies in early childhood education play a crucial role in supporting children’s holistic development and well-being. The global shift in educational paradigms emphasizes children’s well-being as a central indicator of educational quality; however, studies integrating children’s well-being explicitly into learning strategies remain limited. This study aims to analyze learning strategies that support children’s well-being through child-centered learning approaches, safe and inclusive learning environments, and positive social interactions. The research employed a qualitative approach using a literature review with descriptive analysis of scholarly publications related to early childhood education. Data were analyzed through selection, categorization, conceptual synthesis, and thematic interpretation to identify patterns of effective learning strategies. The findings indicate that learning strategies emphasizing active child participation, emotional support, play-based learning, and warm teacher– child relationships significantly enhance children’s emotional, social, and cognitive well-being. This study contributes conceptually by positioning children’s well-being as a pedagogical foundation for designing learning strategies in early childhood education. The findings highlight that integrating well-being into learning practices is essential for creating high- quality, inclusive, and meaningful early childhood learning experiences